Hard X-ray photoelectron spectroscopy study of thermal effect on chemical state of sulfur in rubber compound - K. Ozawa; T. Kakubo; N. Amino; E. Ikenaga (eXPRESS Polymer Letters)
Hard X-ray photoelectron spectroscopy (HAXPES) has been utilized to study chemical state and kinetics of sulfur species in a rubber compound by examining thermally induced changes of S 1s core-level spectra. Two peaks at 2470 and 2472 eV together with the 2479 eV peak from SO42– are resolved in the S 1s spectrum. As the rubber compound is heated at 374, 412, and 440 K, the former two peaks show different thermal behaviors; the peak at 2472 eV is swiftly decreased in its intensity with heating time because of thermal desorption of the sulfur species, whereas the intensity of the 2470 eV peak shows a slight increase especially in the surface region of the rubber compound. On the basis of these thermal behaviors, the peaks at 2470 and 2472 eV are, respectively, associated with S atoms bonded directly to the C atoms and those bonded only to other S atoms. An Arrhenius plot analysis of the 2470 eV peak intensity variation reveals that the S–C bond formation and scission reactions compete with each other with a slightly smaller activation energy in the bond formation than in the bond scission.